Role of Ghnadhara civilization in promoting Education - Sohail, Muhammad; Qadir, Shukria; ullah, Zafar (sourcecoder, 2022)
This paper is about the ancient civilization of Ghandahara and its effect upon educational, social, cultural and archival development in the region. Ghandahara remained the center of great learning for decades and its centres of excellence were constructed in Pushklawati current name Charsadda, Pushapura currently named as Peshawar and Taxilka now named as Taxila. These centers of great learning imparted education in the indigenous style. The word "Gandhara" is frequently mentioned in the vast courtyard of history. Infect, the word is derived from two Sanskrit words "Gand" and "Hara", meaning "fragrance" and "area" respectively. This area is famous for its flowers and buds. This concept extends to the fragrance of flowers found in the valleys of three areas connected with Gandhara, Yodhiana (Swat), Kanshakpura (Parashpura), Peshawar and Pashkalavati (Charsadda). The word Gandhara is first used in the Rig Veda where it is used for the northeastern border of India. Is. Later credible quotes for Gandhara ‘Apastamba Apastamba’ Saravata Sutras Haramaxi srauts.